Solid electrolyte material and battery using the same
By designing solid electrolyte materials composed of Li, Ca, Y, Gd, X, O and H, the problems of low lithium ion conductivity and insufficient safety in the prior art are solved, and high lithium ion conductivity and excellent safety are achieved all solid battery material.
Patent Information
- Application Number
- CN202180021493.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-01-29
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-01-29
AI Technical Summary
Existing solid electrolyte materials perform poorly in lithium ion conductivity, and sulfide solid electrolytes may produce hydrogen sulfide when exposed to the atmosphere, affecting safety.
Using solid electrolyte material composed of Li, Ca, Y, Gd, X, O and H, where X is F, Cl, Br or I, the total molar ratio of O and Y and Gd is greater than 0 and less than 0.82, the design is made. Materials with high lithium ion conductivity and improve their ion conductivity and safety through specific synthetic methods and structural optimization.
A solid electrolyte material with high lithium ion conductivity ensures the safety of the material without hydrogen sulfide production, and is suitable for high-performance all-solid batteries.
Smart Images

Figure CN115280427B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid electrolyte material and a battery using the solid electrolyte material. Background Art
[0002] Patent Document 1 discloses a solid-state battery using a sulfide solid electrolyte. Patent Document 2 discloses a solid-state battery using Li 6-3z Y z X 6 (satisfying 0<z<2, and X is Cl or Br).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-129312
[0006] Patent Document 2: International Publication No. 2018 / 025582 Summary of the invention
[0007] Problems to be solved by the invention
[0008] An object of the present disclosure is to provide a solid electrolyte material having high lithium ion conductivity (also referred to as lithium ion electrical conductivity, lithium ion electrical conductivity).
[0009] Means for solving problems
[0010] The solid electrolyte material disclosed herein is composed of Li, Ca, Y, Gd, X, O and H, wherein X is at least one selected from F, Cl, Br and I, and the molar ratio of O to the total of Y and Gd is greater than 0 and less than 0.82.
[0011] Effects of the Invention
[0012] The present disclosure provides a solid electrolyte material having high lithium ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 A cross-sectional view of a battery 1000 according to a second embodiment is shown.
[0014] Figure 2 It is a graph showing X-ray diffraction patterns of the solid electrolyte materials of Examples 1 to 3 and Comparative Example 1.
[0015] Figure 3 It is a schematic diagram of a press-forming die 300 for evaluating the ion conductivity of a solid electrolyte material.
[0016] Figure 4It is a graph showing a Cole-Cole diagram of the impedance measurement result of the solid electrolyte material of Example 1.
[0017] Figure 5 It is a graph showing infrared absorption spectra of the solid electrolyte materials of Examples 1 to 3, Comparative Example 1, and Reference Example 1.
[0018] Figure 6 Graphs showing initial discharge characteristics of the batteries of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0019] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0020] (First embodiment)
[0021] The solid electrolyte material of the first embodiment is composed of Li, Ca, Y, Gd, X, O and H. Among them, X is at least one selected from F, Cl, Br and I. The molar ratio of O to the total of Y and Gd is greater than 0 and less than 0.82. The solid electrolyte material of the first embodiment has high lithium ion conductivity. The so-called high lithium ion conductivity is, for example, 1×10 -5 S / cm or more. That is, the solid electrolyte material of the first embodiment may have, for example, 1×10 -5 S / cm or higher ion conductivity.
[0022] The solid electrolyte material of the first embodiment can be used to obtain an all-solid battery having excellent charge and discharge characteristics. The all-solid battery may be a primary battery or a secondary battery.
[0023] The solid electrolyte material of the first embodiment preferably does not contain sulfur. A solid electrolyte material that does not contain sulfur does not generate hydrogen sulfide even when exposed to the atmosphere, and therefore has excellent safety. The sulfide solid electrolyte disclosed in Patent Document 1 generates hydrogen sulfide when exposed to the atmosphere.
[0024] The solid electrolyte material of the first embodiment may be substantially composed of Li, Ca, Y, Gd, X, O and H. The so-called "the solid electrolyte material of the first embodiment is substantially composed of Li, Ca, Y, Gd, X, O and H" means that in the solid electrolyte material of the first embodiment, the molar ratio (i.e., molar fraction) of the total amount of substances of Li, Ca, Y, Gd, X, O and H to the total amount of substances of all elements constituting the solid electrolyte material is 90% or more. As an example, the molar ratio may also be 95% or more. The solid electrolyte material of the first embodiment may be composed only of Li, Ca, Y, Gd, X, O and H.
[0025] In order to improve the ion conductivity of the solid electrolyte material, X may also be Cl or Br.
[0026] In order to improve the ion conductivity of the solid electrolyte material, the solid electrolyte material of the first embodiment may further contain at least one selected from Sr, Ba, Al, Sc, Ga, Bi, La, Zr, Hf, Ta and Nb.
[0027] The transition metal contained in the solid electrolyte material of the present embodiment may be only Y and Gd, in addition to the elements contained as inevitable impurities.
[0028] In order to improve the ion conductivity of the solid electrolyte material, O bonded to H may exist in the surface region of the solid electrolyte material of the first embodiment.
[0029] Here, the surface region of the solid electrolyte material in the first embodiment refers to a region from the surface of the solid electrolyte material to a depth of about 1 μm in the inner direction.
[0030] The X-ray diffraction pattern of the solid electrolyte material of the first embodiment can be obtained using Cu-Kα rays. In the obtained X-ray diffraction pattern, peaks may also exist in the range of diffraction angles 2θ of 14.9° to 16.0°, 16.3° to 17.4°, 22.4° to 23.5°, 27.2° to 28.2°, 28.3° to 29.3°, 30.0° to 31.1°, 32.2° to 33.4°, 39.2° to 40.4°, and 47.0° to 48.2°. Such a solid electrolyte material has high ion conductivity.
[0031] In order to improve the ion conductivity of the solid electrolyte material, the following four mathematical formulas may also be satisfied.
[0032] 2.4≤x≤3.2,
[0033] 0.06≤y≤0.08,
[0034] 1.5≤z≤2.0, and
[0035] 3.6≤w≤4.6.
[0036] in,
[0037] x represents the molar ratio of Li to the total of Y and Gd,
[0038] y represents the molar ratio of Ca to the total of Y and Gd,
[0039] z represents the molar ratio of Br to the total of Y and Gd,
[0040] w represents the molar ratio of Cl to the total of Y and Gd.
[0041] In order to further improve the ion conductivity of the solid electrolyte material, the following four mathematical formulas may also be satisfied.
[0042] 2.8≤x≤2.9,
[0043] 0.06≤y≤0.08,
[0044] 1.7≤z≤1.8, and
[0045] 4.0≤w≤4.2.
[0046] In order to improve the ion conductivity of the solid electrolyte material, the molar ratio of O to the total of Y and Gd may be greater than 0 and not more than 0.37.
[0047] In order to improve the ion conductivity of the solid electrolyte material, the molar ratio of O to the total of Y and Gd may be greater than 0 and less than 0.15. The molar ratio of O to the total of Y and Gd may be greater than 0 and less than 0.08.
[0048] The shape of the solid electrolyte material of the first embodiment is not limited. Examples of the shape include needle-like, spherical, or ellipsoidal. The solid electrolyte material of the first embodiment may also be particles. The solid electrolyte material of the first embodiment is formed in a particle or plate shape.
[0049] When the shape of the solid electrolyte material of the first embodiment is a particle shape (for example, a spherical shape), the solid electrolyte material of the first embodiment may have a median particle size of 0.1 μm or more and 100 μm or less.
[0050] In order to improve the ion conductivity of the solid electrolyte material of the first embodiment and to disperse the solid electrolyte material and active material of the first embodiment well, the median particle size may be greater than 0.5 μm and less than 10 μm. In order to disperse the solid electrolyte material and active material of the first embodiment better, the solid electrolyte material of the first embodiment may have a smaller median particle size than the active material. The so-called median particle size refers to the particle size when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution can be measured by a laser diffraction measuring device or an image analysis device.
[0051] <Method for producing solid electrolyte material>
[0052] The solid electrolyte material of the first embodiment can be produced by the following method.
[0053] First, a plurality of halides are mixed as raw material powders.
[0054] As an example, when a solid electrolyte material composed of Li, Ca, Y, Gd, Br, Cl, O and H is prepared, LiCl raw material powder, LiBr raw material powder, YCl 3 Raw material powder, GdCl 3 Raw material powder and CaBr 2 Mix. The obtained mixed powder is fired in an inert gas atmosphere (e.g., an argon atmosphere with a dew point of -60°C or less) with adjusted oxygen concentration and water concentration. The firing temperature may be, for example, in the range of 200°C to 650°C. The obtained fired product is allowed to stand in an atmosphere with a relatively high dew point (e.g., a dry atmosphere with a dew point of -30°C).
[0055] The raw material powders may be mixed at a molar ratio pre-adjusted in a manner to offset the composition changes that may occur in the synthesis process. The amount of oxygen in the solid electrolyte material is determined by selecting the raw material powders, the oxygen concentration in the atmosphere, the water concentration in the atmosphere, and the reaction time. In this manner, the solid electrolyte material of the first embodiment is obtained.
[0056] The raw material powder to be mixed may also be oxides and halides. For example, Y 2 O 3 , Gd 2 O 3 NH 4 Cl, NH 4 Br, LiCl, LiBr and CaBr 2 .
[0057] It is considered that oxygen constituting the solid electrolyte material of the first embodiment is introduced from the above-mentioned atmosphere having a relatively high dew point.
[0058] (Second embodiment)
[0059] The second embodiment will be described below. Matters described in the first embodiment may be omitted.
[0060] The battery of the second embodiment comprises a positive electrode, a negative electrode and an electrolyte layer. The electrolyte layer is arranged between the positive electrode and the negative electrode. At least one selected from the positive electrode, the electrolyte layer and the negative electrode contains the solid electrolyte material of the first embodiment. The battery of the second embodiment has excellent charge and discharge characteristics because it contains the solid electrolyte material of the first embodiment. The battery can also be an all-solid battery.
[0061] Figure 1 A cross-sectional view of a battery 1000 according to a second embodiment is shown.
[0062] The battery 1000 includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 . The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .
[0063] The positive electrode 201 includes positive electrode active material particles 204 and solid electrolyte particles 100 .
[0064] The electrolyte layer 202 contains an electrolyte material (eg, a solid electrolyte material).
[0065] The negative electrode 203 includes negative electrode active material particles 205 and solid electrolyte particles 100 .
[0066] The solid electrolyte particles 100 are particles made of the solid electrolyte material of the first embodiment, or particles containing the solid electrolyte material of the first embodiment as a main component. The particles containing the solid electrolyte material of the first embodiment as a main component refer to particles in which the solid electrolyte material of the first embodiment is contained as the largest component by mass ratio.
[0067] The positive electrode 201 contains a material that can intercalate and deintercalate metal ions (eg, lithium ions), such as a positive electrode active material (eg, positive electrode active material particles 204 ).
[0068] Examples of positive electrode active materials are lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal fluorides, transition metal oxysulfides or transition metal oxynitrides. Examples of lithium-containing transition metal oxides are LiNi 1-d-f Co d Al f O 2 (where 0<d, 0<f, and 0<(d+f)<1) or LiCoO 2 .
[0069] In the positive electrode 201, in order to make the positive electrode active material particles 204 and the solid electrolyte particles 100 well dispersed, the positive electrode active material particles 204 may also have a median particle size of 0.1 μm or more. Through this good dispersion, the charge and discharge characteristics of the battery 1000 are improved. In order to make lithium diffuse rapidly in the positive electrode active material particles 204, the positive electrode active material particles 204 may also have a median particle size of 100 μm or less. Because of the rapid diffusion of lithium, the battery 1000 can operate at high power. As described above, the positive electrode active material particles 204 may also have a median particle size of 0.1 μm or more and 100 μm or less.
[0070] In the positive electrode 201 , in order to disperse the positive electrode active material particles 204 and the solid electrolyte particles 100 well, the positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100 .
[0071] To improve the energy density and power of the battery 1000 , in the positive electrode 201 , the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0072] In order to increase the energy density and power of the battery 1000 , the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.
[0073] The electrolyte layer 202 contains an electrolyte material. The electrolyte material may be the solid electrolyte material of the first embodiment. The electrolyte layer 202 may be a solid electrolyte layer.
[0074] The electrolyte layer 202 may be composed only of the solid electrolyte material of the first embodiment. Alternatively, the electrolyte layer 202 may be composed only of a solid electrolyte material different from the solid electrolyte material of the first embodiment.
[0075] An example of a solid electrolyte material different from the solid electrolyte material of the first embodiment is Li 2 MgX' 4 , Li 2 FeX' 4 、Li(Al、Ga、In)X' 4 , Li 3 (Al, Ga, In)X' 6 or LiI. wherein X' is at least one selected from F, Cl, Br and I.
[0076] In the present disclosure, “(A, B, C)” means “at least one selected from A, B, and C”.
[0077] Hereinafter, the solid electrolyte material of the first embodiment is referred to as a first solid electrolyte material. A solid electrolyte material different from the solid electrolyte material of the first embodiment is referred to as a second solid electrolyte material.
[0078] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed. The layer formed by the first solid electrolyte material and the layer formed by the second solid electrolyte material may also be stacked along the stacking direction of the battery 1000.
[0079] In order to suppress short circuit between the positive electrode 201 and the negative electrode 203 and improve the power of the battery 1000 , the electrolyte layer 202 may have a thickness of 1 μm or more and 100 μm or less.
[0080] The negative electrode 203 contains a material capable of inserting and removing metal ions (eg, lithium ions), such as a negative electrode active material (eg, negative electrode active material particles 205 ).
[0081] Examples of negative electrode active materials are metal materials, carbon materials, oxides, nitrides, tin compounds or silicon compounds. The metal material may be a single metal or an alloy. Examples of metal materials are lithium metal or lithium alloys. Examples of carbon materials are natural graphite, coke, graphitized carbon, carbon fiber, spherical carbon, artificial graphite or amorphous carbon. From the viewpoint of capacity density, preferred examples of negative electrode active materials are silicon (i.e., Si), tin (i.e., Sn), silicon compounds or tin compounds.
[0082] In the negative electrode 203, in order to make the negative electrode active material particles 205 and the solid electrolyte particles 100 well dispersed, the negative electrode active material particles 205 may also have a median particle size of 0.1 μm or more. Through this good dispersion, the charge and discharge characteristics of the battery are improved. In order to make lithium diffuse rapidly in the negative electrode active material particles 205, the negative electrode active material particles 205 may also have a median particle size of 100 μm or less. Because of the rapid diffusion of lithium, the battery can operate at high power. As described above, the negative electrode active material particles 205 may also have a median particle size of 0.1 μm or more and 100 μm or less.
[0083] In the negative electrode 203 , in order to disperse the negative electrode active material particles 205 and the solid electrolyte particles 100 well, the negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100 .
[0084] In order to improve the energy density and power of the battery 1000 , in the negative electrode 203 , the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0085] In order to increase the energy density and power of the battery 1000 , the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.
[0086] In order to improve ion conductivity, chemical stability, and electrochemical stability, at least one selected from the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a second solid electrolyte material.
[0087] As described above, the second solid electrolyte material may also be a halide solid electrolyte. An example of a halide solid electrolyte is Li 2 MgX' 4 , Li 2 FeX' 4 、Li(Al、Ga、In)X' 4 , Li 3 (Al, Ga, In)X' 6 or LiI. wherein X' is at least one selected from F, Cl, Br and I.
[0088] The second solid electrolyte material may be a sulfide solid electrolyte.
[0089] An example of a sulfide solid electrolyte is Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 SB 2 S 3 , Li 2 S-GeS 2 , Li 3.25 Ge 0.25 P 0.75 S 4 or Li 10 G 2 S 12 .
[0090] The second solid electrolyte material may be an oxide solid electrolyte.
[0091] Examples of oxide solid electrolytes are:
[0092] (i)LiTi 2 (PO 4 ) 3 or NASICON type solid electrolytes such as those substituted with other elements thereof,
[0093] (ii) (LaLi)TiO 3 Such perovskite solid electrolytes,
[0094] (iii)Li 14 ZnGe 4 O 16 , Li 4 SiO 4 、LiGeO 4 or LISICON type solid electrolytes such as those substituted with other elements thereof,
[0095] (iv)Li 7La 3 Zr 2 O 12 or a garnet-type solid electrolyte such as an element substituted product thereof, or
[0096] (v)Li 3 PO 4 or its N-substituted product.
[0097] The second solid electrolyte material may also be an organic polymer solid electrolyte.
[0098] Examples of organic polymer solid electrolytes include compounds of polymer compounds and lithium salts. The polymer compounds may also have an ethylene oxide structure. The polymer compounds having an ethylene oxide structure contain more lithium salts, so that the ion conductivity can be further improved.
[0099] An example of a lithium salt is LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiSO 3 CF 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ) or LiC(SO 2 CF 3 ) 3 One lithium salt selected from the above may be used alone. Alternatively, a mixture of two or more lithium salts selected from the above may be used.
[0100] At least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a non-aqueous electrolyte, a gel electrolyte, or an ionic liquid for the purpose of facilitating the transfer of lithium ions and improving the power characteristics of the battery 1000 .
[0101] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.
[0102] Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents or fluorinated solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorinated solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, ethyl fluoromethyl carbonate or dimethylene fluorocarbonate. One non-aqueous solvent selected from the above may be used alone. Alternatively, a mixture of two or more non-aqueous solvents selected from the above may be used.
[0103] An example of a lithium salt is LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiSO 3 CF 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ) or LiC(SO 2 CF 3 ) 3 One lithium salt selected from the above may be used alone. Alternatively, a mixture of two or more lithium salts selected from the above may be used.
[0104] The concentration of the lithium salt is, for example, in the range of 0.5 mol / L to 2 mol / L.
[0105] As the gel electrolyte, a polymer material impregnated with a non-aqueous electrolyte can be used. Examples of the polymer material are polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.
[0106] Examples of cations contained in ionic liquids are:
[0107] (i) Aliphatic chain quaternary salts (quaternary salts) such as tetraalkylammonium or tetraalkylphosphonium,
[0108] (ii) an aliphatic cyclic ammonium such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium or piperidinium, or
[0109] (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium cations.
[0110] An example of an anion contained in the ionic liquid is PF 6 - , BF 4 - , SbF 6 - , AsF 6 - 、SO 3 CF 3 - 、N(SO 2 CF 3 ) 2 - 、N(SO 2 C 2 F 5 ) 2 - 、N(SO 2 CF 3 )(SO 2 C 4 F 9 ) - or C(SO 2 CF 3 ) 3 - .
[0111] The ionic liquid may also contain a lithium salt.
[0112] At least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a binder for the purpose of improving the adhesion between particles.
[0113] Examples of binders are polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aromatic polyamide resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene-butadiene rubber or carboxymethyl cellulose.
[0114] In addition, copolymers can also be used as binders. Examples of such binders are copolymers of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, trifluorochloroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene. A mixture of two or more materials selected from the above can also be used as a binder.
[0115] In order to improve electronic conductivity, at least one of the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent.
[0116] Examples of conductive additives are:
[0117] (i) Graphites such as natural graphite or artificial graphite,
[0118] (ii) Carbon blacks such as acetylene black or Ketjen black,
[0119] (iii) Conductive fibers such as carbon fibers or metal fibers,
[0120] (iv) fluorinated carbon,
[0121] (v) Metal powders such as aluminum,
[0122] (vi) Conductive whiskers such as zinc oxide or potassium titanate,
[0123] (vii) conductive metal oxides such as titanium oxide, or
[0124] (viii) Conductive polymer compounds such as polyaniline, polypyrrole or polythiophene.
[0125] For cost reduction, the conductive auxiliary agent (i) or (ii) mentioned above may be used.
[0126] Examples of the shape of the battery of the second embodiment include a coin shape, a cylindrical shape, a square shape, a sheet shape, a button shape, a flat shape, or a laminated shape.
[0127] The battery of the second embodiment can also be manufactured, for example, by preparing materials for forming a positive electrode, materials for forming an electrolyte layer, and materials for forming a negative electrode, and producing a stacked body in which the positive electrode, the electrolyte layer, and the negative electrode are stacked in this order by a known method.
[0128] Example
[0129] Hereinafter, the present disclosure will be described in more detail with reference to examples.
[0130] (Example 1)
[0131] [Production of solid electrolyte materials]
[0132] In an argon atmosphere having a dew point of -60°C or less and an oxygen concentration of 0.0001 vol% or less (hereinafter referred to as a "dry argon atmosphere"), the LiCl:LiBr:YCl 3 :GdCl 3 :CaBr 2 =1:1.85:0.5:0.5:0.075 molar ratio of LiCl, LiBr and YCl 3 , GdCl 3 and CaBr 2 As raw material powder. These raw material powders are crushed and mixed in a mortar. After the obtained mixture is fired in an alumina crucible at 500°C for 1 hour, it is crushed in a mortar. The obtained fired product is allowed to stand for about 10 minutes in a dry atmosphere having a dew point of -30°C and an oxygen concentration of less than 20.9 volume%. In this way, the solid electrolyte material of Example 1 is obtained.
[0133] [Composition analysis of solid electrolyte materials]
[0134] The contents of Li, Ca, Y and Gd per unit weight of the solid electrolyte material of Example 1 were measured by high-frequency inductively coupled plasma emission spectrometry using a high-frequency inductively coupled plasma emission spectrometry device (manufactured by Thermo Fisher Scientific, iCAP7400). The contents of Cl and Br in the solid electrolyte material of Example 1 were measured by ion chromatography using an ion chromatograph device (manufactured by Dionex, ICS-2000). Based on the contents of Li, Ca, Y, Gd, Br and Cl, the molar ratio of Li:Ca:Y:Gd:Br:Cl was calculated. As a result, the solid electrolyte material of Example 1 had a molar ratio of Li:Ca:Y:Gd:Br:Cl of 2.85:0.07:0.50:0.50:1.75:4.07.
[0135] The mass ratio of O to the entire solid electrolyte material of Example 1 was measured by non-dispersive infrared absorption method using an oxygen-nitrogen-hydrogen analyzer (manufactured by Horiba, Ltd., EMGA-930). As a result, the mass ratio of O was 0.29%. Based on this, the (Y+Gd):O molar ratio was calculated. As a result, the solid electrolyte material of Example 1 had a (Y+Gd):O molar ratio of 1.00:0.08.
[0136] In the composition analysis, elements having a molar fraction of 0.01% or less relative to the total of Y and Gd are regarded as impurities.
[0137] [Infrared spectroscopy]
[0138] The solid electrolyte material of Example 1 was analyzed by total reflection measurement using an infrared spectrometer (manufactured by BRUKER, ALPHA). A prism made of diamond was used. As a result, in the case of protons (H + ) and oxygen at 3100cm -1 ~3640cm -1 The peak is detected in the region of . The surface region in the present disclosure refers to the region measured by such an operation. That is, the thickness of the surface region of the solid electrolyte material of the first embodiment is about 1 μm from the surface to the inside of the solid electrolyte material. Figure 5 3 is a graph showing the infrared absorption spectrum of the solid electrolyte material of Example 1.
[0139] [X-ray diffraction]
[0140] The crystal structure of the solid electrolyte material was analyzed using an X-ray diffraction device (Rigaku Co., Ltd., MiniFlex 600). The X-ray diffraction pattern of the solid electrolyte material of Example 1 was measured in a dry environment with a dew point of -45°C or less. Cu-Kα rays (wavelength 200 nm) were used as the X-ray source. and ).
[0141] As a result of X-ray diffraction measurement, peaks were present at 15.44°, 16.83°, 22.95°, 27.78°, 28.80°, 30.59°, 32.82°, 39.79°, and 47.62°. Figure 2 3 is a graph showing an X-ray diffraction pattern of the solid electrolyte material of Example 1.
[0142] [Evaluation of ion conductivity]
[0143] Figure 3 It is a schematic diagram of a press-forming die 300 for evaluating the ion conductivity of a solid electrolyte material.
[0144] The press forming die 300 includes a punch upper portion 301, a frame die 302, and a punch lower portion 303. The frame die 302 is formed of insulating polycarbonate. The punch upper portion 301 and the punch lower portion 303 are both formed of electron conductive stainless steel.
[0145] use Figure 3 The press molding die 300 shown was used to measure the ion conductivity of the solid electrolyte material of Example 1 by the following method.
[0146] In a dry argon atmosphere, the powder 101 of the solid electrolyte material of Example 1 was filled into the press mold 300. Inside the press mold 300, a pressure of 400 MPa was applied to the solid electrolyte material of Example 1 using the punch upper portion 301 and the punch lower portion 303.
[0147] The punch upper part 301 and the punch lower part 303 were connected to a potentiostat (Princeton Applied Research, versaSTAT4) in a state where pressure was applied. The punch upper part 301 was connected to the working electrode and the potential measurement terminal. The punch lower part 303 was connected to the counter electrode and the reference electrode. The impedance of the solid electrolyte material of Example 1 was measured by electrochemical impedance spectroscopy at room temperature.
[0148] Figure 4 It is a graph showing a Cole-Cole diagram of the impedance measurement result of the solid electrolyte material of Example 1.
[0149] Figure 4 The real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte material to ion conduction. For this real value, please refer to Figure 4 The arrow R shown in SE Using this resistance value, the ion conductivity was calculated based on the following mathematical formula (1).
[0150] σ=(R SE ×S / t) -1 (1)
[0151] Wherein, σ represents the ion conductivity. S represents the contact area between the solid electrolyte material and the punch upper portion 303 ( Figure 3 The cross-sectional area of the hollow part of the frame mold 301 is equal to that of the hollow part of the frame mold 301). SE represents the resistance value of the solid electrolyte material during impedance measurement. t represents the thickness of the solid electrolyte material to which pressure is applied ( Figure 3 , which is equal to the thickness of the layer formed by the powder 101 of the solid electrolyte material).
[0152] The ionic conductivity of the solid electrolyte material of Example 1 measured at 25°C was 7.2×10 -4 S / cm.
[0153] [Battery production]
[0154] In a dry argon atmosphere, the solid electrolyte material of Example 1 and the active material, namely LiCoO, were prepared in a volume ratio of 30:70. 2 These materials were mixed in an agate mortar and pestle. The operation was performed in this manner to obtain a mixture.
[0155] In an insulating cylinder having an inner diameter of 9.5 mm, the solid electrolyte material of Example 1 (100 mg), the above-mentioned mixture (10.0 mg) and aluminum powder (14.7 mg) were stacked in sequence. A pressure of 300 MPa was applied to the stack to form the first electrode and the solid electrolyte layer. The solid electrolyte layer had a thickness of 500 μm.
[0156] Next, a metal In foil was stacked on the solid electrolyte layer. The solid electrolyte layer was sandwiched between the metal In foil and the first electrode. The metal In foil had a thickness of 200 μm. Next, a pressure of 80 MPa was applied to the metal In foil to form the second electrode.
[0157] A current collector made of stainless steel was mounted on the first electrode and the second electrode, and then a current collecting lead was mounted on the current collector. Finally, an insulating ferrule was used to isolate the inside of the insulating tube from the outside atmosphere, so that the inside of the tube was sealed. In this way, the battery of Example 1 was obtained.
[0158] [Charge and discharge test]
[0159] Figure 6 This is a graph showing the initial discharge characteristics of the battery of Example 1. Figure 6 The results shown were determined by the following method.
[0160] The battery of Example 1 was placed in a thermostatic chamber at 25°C. 2 The battery of Example 1 was charged to a voltage of 3.7 V at a current density of 89 μA / cm 2 The battery of Example 1 was discharged at a current density of to a voltage of 1.9 V.
[0161] As a result of the charge and discharge test, the battery of Example 1 had an initial discharge capacity of 500 μAh.
[0162] (Examples 2 and 3)
[0163] In Example 2, the solid electrolyte material of Example 2 was obtained in the same manner as in Example 1 except that the reaction product was left to stand in a dry atmosphere having a dew point of -30°C and an oxygen concentration of 20.9 vol % or less for 30 minutes instead of about 10 minutes.
[0164] In Example 3, the time for the calcined product to stand in a dry atmosphere having a dew point of -30°C and an oxygen concentration of 20.9 vol % or less was set to about 1 hour instead of about 10 minutes. The solid electrolyte material of Example 3 was obtained in the same manner as in Example 1 except for this.
[0165] The element ratio (molar ratio), infrared absorption spectrum, X-ray diffraction and ion conductivity of the solid electrolyte materials of Examples 2 and 3 were measured in the same manner as in Example 1. The measurement results are shown in Tables 1 and 2. Figure 2 Graphs showing X-ray diffraction patterns of the solid electrolyte materials of Examples 2 and 3. Figure 5 This is a graph showing the infrared absorption spectra of the solid electrolyte materials of Examples 2 and 3.
[0166] The mass ratios of O with respect to the entire solid electrolyte material in Examples 2 and 3 were 0.57% and 1.33%, respectively.
[0167] The solid electrolyte materials of Examples 2 and 3 were used in the same manner as in Example 1 to obtain batteries of Examples 2 and 3.
[0168] Using the batteries of Examples 2 and 3, the charge and discharge test was carried out in the same manner as in Example 1. The batteries of Examples 2 and 3 were charged and discharged in the same manner as in Example 1.
[0169] (Comparative Example 1)
[0170] In Comparative Example 1, the solid electrolyte material of Comparative Example 1 was obtained in the same manner as in Example 1 except that the time for leaving the calcined product in a dry atmosphere having a dew point of -30°C and an oxygen concentration of 20.9 vol % or less was set to about 6 hours instead of about 10 minutes.
[0171] The element ratio (molar ratio), infrared absorption spectrum, X-ray diffraction and ion conductivity of the solid electrolyte material of Comparative Example 1 were measured in the same manner as in Example 1. The measurement results are shown in Tables 1 and 2. Figure 2 3 is a graph showing an X-ray diffraction pattern of the solid electrolyte material of Comparative Example 1. Figure 5 3 is a graph showing the infrared absorption spectrum of the solid electrolyte material of Comparative Example 1.
[0172] The mass ratio of O to the entire solid electrolyte material in Comparative Example 1 was 2.91%.
[0173] The solid electrolyte material of Comparative Example 1 was used and the same operation as in Example 1 was carried out to obtain a battery of Comparative Example 1.
[0174] The battery of Comparative Example 1 was used to perform a charge and discharge test in the same manner as in Example 1. The battery of Comparative Example 1 had an initial discharge capacity of only 1 μAh or less. That is, the battery of Comparative Example 1 was neither charged nor discharged. Figure 6 This is a graph showing the initial discharge characteristics of the battery of Comparative Example 1.
[0175] (Reference Example 1)
[0176] In Reference Example 1, the fired product was not left to stand in a dry atmosphere having a dew point of -30°C and an oxygen concentration of 20.9 vol % or less. A solid electrolyte material of Reference Example 1 was obtained in the same manner as in Example 1 except for the above.
[0177] In the same manner as in Example 1, infrared spectroscopic analysis of the solid electrolyte material of Reference Example 1 was performed. Figure 5 3 is a graph showing the infrared absorption spectrum of the solid electrolyte material of Reference Example 1.
[0178] Table 1
[0179]
[0180] Table 2
[0181]
[0182] Investigation
[0183] As shown in Table 1, the solid electrolyte materials of Examples 1 to 3 have a 1×10 -5 High ion conductivity of S / cm or more.
[0184] As can be seen from Examples 1 to 3, if the molar ratio of O to the sum of Y and Gd is greater than 0 and less than 0.37, the solid electrolyte material has a 1×10 -5 It is believed that if the above molar ratio is greater than 0 and less than 0.08, the solid electrolyte material has a 1×10 -4 S / cm or higher ion conductivity.
[0185] from Figure 5 It was confirmed that the solid electrolyte materials of Examples 1 to 3 have oxygen bonded to protons. On the other hand, it was confirmed that the solid electrolyte material of Reference Example 1 does not contain oxygen bonded to protons. Based on these results, it is believed that when the solid electrolyte material is exposed to an atmosphere with a relatively high dew point, moisture in the atmosphere is introduced into the solid electrolyte material. It is believed that the oxygen bonded to protons exists as hydroxyl groups or hydrated water.
[0186] The batteries of Examples 1 to 3 were charged and discharged at 25°C.
[0187] Since the solid electrolyte materials of Examples 1 to 3 do not contain sulfur, hydrogen sulfide is not generated.
[0188] As described above, the solid electrolyte material of the present disclosure is suitable for providing a battery having high lithium ion conductivity and capable of good charge and discharge.
[0189] Industrial Applicability
[0190] The solid electrolyte material disclosed in the present invention can be used in, for example, an all-solid lithium-ion secondary battery.
[0191] Explanation of symbols
[0192] 100: Solid electrolyte particles
[0193] 101: Powder of solid electrolyte material
[0194] 201: Positive electrode
[0195] 202: Electrolyte layer
[0196] 203: Negative electrode
[0197] 204: Positive electrode active material particles
[0198] 205: Negative electrode active material particles
[0199] 300: Pressurized forming die
[0200] 301: Upper part of punch
[0201] 302: Frame mold
[0202] 303: Punch lower part
[0203] 1000: Battery
Claims
1. A solid electrolyte material consisting of Li, Ca, Y, Gd, X, O and H, in, X is at least one selected from F, Cl, Br and I, The molar ratio of O to the total of Y and Gd is greater than 0 and less than 0.82, The solid electrolyte material satisfies the following four mathematical formulas: 2.4≤x≤3.2、 0.06≤y≤0.08、 1.5≤z≤2.0, and 3.6≤w≤4.6, in, x represents the molar ratio of Li to the total of Y and Gd, y represents the molar ratio of Ca to the total of Y and Gd, z represents the molar ratio of Br to the total of Y and Gd, w represents the molar ratio of Cl to the total of Y and Gd.
2. The solid electrolyte material according to claim 1, wherein X is Cl and Br.
3. The solid electrolyte material according to claim 1 or 2, further comprising at least one selected from the group consisting of Sr, Ba, Al, Sc, Ga, Bi, La, Zr, Hf, Ta and Nb.
4. The solid electrolyte material according to claim 1 or 2, wherein In the surface region of the solid electrolyte material, O combined with H exists.
5. The solid electrolyte material according to claim 1 or 2, wherein in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα rays, there are peaks in the ranges of diffraction angles 2θ of 14.9° to 16.0°, 16.3° to 17.4°, 22.4° to 23.5°, 27.2° to 28.2°, 28.3° to 29.3°, 30.0° to 31.1°, 32.2° to 33.4°, 39.2° to 40.4°, and 47.0° to 48.2°.
6. The solid electrolyte material according to claim 1 or 2, wherein 2.8≤x≤2.9、 1.7≤z≤1.8, and 4.0≤w≤4.2。 7 . The solid electrolyte material according to claim 1 , wherein a molar ratio of O to the total of Y and Gd is greater than 0 and not more than 0.
37.
8. A battery comprising: positive electrode; a negative electrode; and an electrolyte layer disposed between the positive electrode and the negative electrode, in, At least one selected from the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 7.
